Salvia sclarea L. - potential anti-inflammatory agent in the therapy of periodontitis - Randjelović, Milica; Išljamović, Milica; Petrović, Aleksandar; Milutinović, Milica; Miladinović, Bojana; Branković, Suzana; Kitić, Nemanja; Kitić, Dušanka (Archives of Pharmacy, 2022)
The aim of the study was to examine the effects of a dried extract (ethanol 80% V/V, DSR 1:10) of the above-ground parts of clary sage, Salvia sclarea L. at the full flowering stage, on a model of lipopolysaccharide (LPS) induced periodontitis in rats. Inflammation was induced by applying of 1 µL of LPS solution (10 µg/µL) twice during the experiment (ten days) in the interdental papilla between the first and second right maxillary molars. The extract, dissolved in water, was administered twice a day per os, by oral gavage, in a single dose of 200 mg/kg of body weight. In control groups (I and II), which were injected with saline and treated with water or the extract, morphological changes on hematoxylin-eosin preparations of periodontium were completely consistent with healthy tissue. Histopathological analysis of rats with induced periodontitis treated with water (group III) showed significant changes characterized by the dilation of blood vessels in the periodontium, an increase in the number of neutrophils and lymphocytes in the gingiva and the resorption of the alveolar bone. In rats from groups IV and V with induced periodontitis treated with the extract or preventively with the extract three days before the induction of inflammation, a significantly smaller number of inflammatory cells was observed and a larger number of fibroblasts, without signs of bone resorption. The clary sage extract showed significant anti-inflammatory activity with the potential to have a prominent place in the treatment of periodontal disease in humans.